Sunset of the sabertooth - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series ;, 1996)
The magic tree house transports Jack and Annie on a mission to the Ice Age where they encounter Cro-Magnons, cave bears, sabertooth tigers, and woolly mammoths.